Effect of vaporized ethyl pyruvate as a novel preservation agent for control of postharvest quality and fungal damage of strawberry and cherry fruits. (January 2016) - Bozkurt, F.; Tornuk, F.; Toker, O.S.; Karasu, S.; Arici, M.; Durak, M.Z.
Abstract: Fresh fruits are perishable products that may be exposed to fungal attack easily after harvesting. In this study, efficiency of different vaporized ethyl pyruvate (EP) concentrations [0 (control), 250, 500 or 1000 μL] on preventing/retarding fungal decay and maintenance overall quality of fresh strawberry and cherry packed in close-lid plastic containers was tested during 6 days of storage at 8 °C and 90% relative humidity. Physicochemical, textural and bioactivity of the fruits were also determined. Five hundred microlitres of EP (192 μL/L in air) gave favourable results for retardation of fungal decay and weight loss of the fruits. Ripening of the fruits was slower for the EP treated samples than that of the control, as understood by the total soluble solid levels of the fruits. EP treated fruits maintained their textural properties for longer (P < 0.05) periods than the control sample. Total phenolic contents and DPPH scavenging abilities of the fruits treated with EP were also comparable. In conclusion, this study confirmed that hurdle effect of vaporized EP and cold storage had great potential to retard fungal decay and maintain postharvest quality of perishable fruits such as strawberry and cherry without causing any negative effect on their colour and bioactivity properties affecting consumer preference. Highlights: Cherry and strawberry fruits were treated with ethyl pyruvate (EP) vapours. Fungal decay, weight loss, bioactive and physicochemical parameters were measured. 500 μL EP was satisfactory on retardation of fungal decay and weight loss of fruits. Ripening of the fruits was slowed down by EP treatment.